Born Under a Lucky Star: Financial Aid, College Completion, Labor Supply, and Credit Constraints - Jeffrey T. Denning (Institute of Labor Economics (IZA), 2017)
Financial aid has been shown to affect student outcomes from enrollment to graduation. However, effects on graduation can be driven either by marginal students induced to enroll by financial aid, or by inframarginal students who would have enrolled anyway but received additional financial aid. This paper identifies the effect of financial aid on inframarginal students rather than the combined effect on marginal and inframarginal students by examining a change in financial aid that did not change enrollment. I find that additional financial aid accelerates graduation for university seniors and increases persistence for sophomores and juniors. To do this, I examine a discrete change in the amount of federal financial aid available to financially independent students. I find that financial aid received by needier students is more likely to positively affect educational outcomes.
Keywords: I22; I23; 330; financial aid; graduation